Complex Evaluation Of Quality Indicators Of Two-Layer Knitted Fabrics In New Structure (Texas Journal of Engineering and Technology, 2023)
The article presents comprehensive assessment of the quality indicators of double-layer knitted fabrics of a new structure, produced by needles in rib arrangement, using the technological capabilities of modern double bed knitting machines.